From competition to cure: the development of live biotherapeutic products for anticancer therapy in the iGEM competition - Van den Berghe, Luka; Masschelein, Joleen; Pinheiro, Vitor B. (Frontiers in Bioengineering and Biotechnology, 2024)
Cancer is a leading cause of mortality globally, often diagnosed at advanced stages with metastases already present, complicating treatment efficacy. Traditional treatments like chemotherapy and radiotherapy face challenges such as lack of specificity and drug resistance. The hallmarks of cancer, as defined by Hanahan and Weinberg, describe tumors as complex entities capable of evolving traits that promote malignancy, including sustained proliferation, resistance to cell death, and metastasis.Emerging research highlights the significant role of the microbiome in cancer development and treatment, influencing tumor progression and immune responses. This review explores the potential of live biotherapeutic products (LBPs) for cancer diagnosis and therapy, focusing on projects from the International Genetically Engineered Machines (iGEM) competition that aim to innovate LBPs for cancer treatment. Analyzing 77 projects from 2022, we highlight the progress and ongoing challenges within this research field.